Determinants of Shoe Buying Decisions: A Study on Sports Students’ Preferences - Evanda, Alin; irawan, fajar awang (Universitas Negeri Semarang, 2025)
Students who are active in sports have considerations in choosing the ideal shoes, especially when they are faced with quality, price, and brand image issues simultaneously. This study aims to analyze the determination of shoe purchasing decisions based on shoe quality in sports students. This study uses a quantitative descriptive method with an online form instrument to collect the required data based on expert validation. A total of 95 respondents from sports students who were willing to fill out the form by agreeing to the terms before continuing to fill in the questions asked. The results found that the assessment of shoe quality amounted to an average of 45 people or 47% in the good category. Assessment of the price of sports shoes as many as 50 people with a percentage of 52.63% interpretation is good. The results of the brand image of sports shoes as many as 30 people with a percentage of 31.58% 15 people in the good category. The conclusion in this study found that sports students have careful consideration to choose quality shoes and have a well-known brand image. The decision was taken based on shoes with a good image that have good quality so that they are comfortable to wear. Future research is expected to be able to identify in detail what shoe brands are popular both local and international products that are the choice when exercising.